Kesulitan Mahasiswa Dalam Memahami Konsep Kinematika Gerak 1 Dimensi - Abu Zainuddin; Sentot Kusairi; Siti Zulaikah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This study aims to reveal the difficulties of students in understanding the concept of 1 Dimensional motion kinematics. The research subjects were 38 undergraduate students of UNESA Physics Education semester V class A. The research method used a survey using instruments in the form of 20 reasoned multiple choice questions on the topic of Newtonian Mechanics. In this article the discussion is focused on questions number 2 and number 4 because it indicates the difficulties of students in understanding the concept of 1-dimensional kinematics. From the results of the analysis of the reasons for student answers it is known that students experience difficulties, namely, difficulties in distinguishing position, displacement or distance; difficulty interpreting negative acceleration and is always considered a slowdown.Abstrak: Penelitian ini bertujuan untuk mengungkap kesulitan mahasiswa dalam memahami konsep kinematika gerak 1 Dimensi. Subjek penelitian adalah 38 mahasiswa S1 Pendidikan Fisika UNESA semester V kelas A. Metode penelitian menggunakan survei dengan menggunakan instrumen berupa 20 soal pilihan ganda beralasan pada topik Mekanika Newton. Pada artikel ini pembahasan difokuskan pada soal nomor 2 dan nomor 4 karena mengindikasikan kesulitan mahasiswa dalam memahami konsep kinematika 1 dimensi. Dari hasil analisis alasan jawaban mahasiswa diketahui bahwa mahasiswa mengalami kesulitan yakni, kesulitan dalam membedakan posisi, perpindahan atau jarak; kesulitan memaknai percepatan negatif  dan selalu dianggap sebagai perlambatan.